Follicle Stimulating Hormone Receptor (FSHR) Polymorphisms and Polycystic Ovary Syndrome (PCOS) - Laven, Joop S. E. (Frontiers in Endocrinology, 2019)
PCOS is the commonest endocrine abnormality in women of reproductive age typically presenting with chronic amenorrhea, clinical or biochemical hyperandrogenism and polycystic ovarian morphology. Restoring mono-ovulation is the ultimate goal of ovulation induction and most women do respond to ovulation inducing agents causing their FSH levels to rise. Familial clustering and the results from twin studies strongly support an underlying genetic basis for PCOS. Recent GWA studies have identified several genetic variants being genome wide significantly associated with PCOS. Amongst those are variants in or near the LH and FSH receptor genes as well as a variant in the FSH- gene. Data on the role of FSH-Receptor polymorphisms in PCOS are conflicting. It seems that in large Chinese studies FSH-Receptor polymorphisms are not associated with either PCOS risk or with PCOS treatment outcome. However, in large scale studies in Caucasians these polymorphisms seem to influence the risk of having PCOS. Moreover, these studies also showed that some polymorphisms might affect some clinical features of PCOS as well as treatment outcome. Although most research has focused on the role of FSH-Receptor polymorphisms there seems to be also some evidence showing that SNPs in the LHCG-Receptor as well as those in FSH- gene might also alter the phenotype of PCOS.